Exploring the Dual Therapeutic Potential of a Photoactivatable AIEgen in Cancer and Alzheimer’s Disease - Ghosh, Priyam; Mukhopadhyay, Sayantani; Singh, Mrinalini; Ghosh, Siddhartha Sankar; Iyer, Parameswar Krishnan (Synlett, 2025)
One minimally invasive treatment that may help with Alzheimer’s disease (AD) and cancer is photodynamic therapy (PDT). Side effects are reduced with PDT, which targets cancer cells while preserving healthy tissue. Photo-oxygenation of amyloid-β (Aβ) is considered an efficient way to inhibit Aβ aggregation in AD. In this work, we constructed a photoactivatable aggregation-induced emission probe, 2-(7a-ethoxybenzo[f]indeno[1,2-b]chromen-12(7aH)-ylidene)malononitrile (P1), which exhibited red emission, amyloid targeting ability, good biocompatibility, and photostability, and a remarkable capacity to generate reactive oxygen species. Molecular docking was performed to elucidate the interactions between P1 with Aβ40 and Cathepsin D, confirming its binding efficacy and stability. In vitro studies confirm the therapeutic ability of the probe in PDT. These combined properties highlight the comprehensive dual therapeutic potential of P1 in AD and cancer.
Keywords: AIEgen; multifunctional fluorescent probe; reactive oxygen species; cancer photodynamic therapy; Alzheimer’s disease